Exercise and sleep affect blood pressure and blood sugar of hypertensive patients - Sonia Gulia; C Vasantha Kalyani; Kusum K Rohilla (Wolters Kluwer Medknow Publications, 2023)
Aim: Hypertension is a major worldwide health issue because of its great prevalence. This study's aim was to check the effects of exercise and sleep on blood pressure (BP) and blood sugar among hypertensive patients. Materials and Methods: The study was a descriptive study that was conducted on 545 hypertensive patients at the All India Institute of Medical Sciences, Rishikesh, using validated self-structured questionnaire tools. Results: Hypertensive patients bio-demographic characteristics, sleep, exercise, and physical activity were examined and presented as frequency and percentage. Majority of hypertensive patients were male (55%), illiterate (25%), and their sleeping were OK during the night (38%). Their mean systolic BP (SBP) was 156.17 ± 15.83 mmHg, the diastolic BP was 91.81 ± 12.93 mmHg, and random blood sugar was 127.27 ± 6.06 g/dl, respectively. Among hypertensive patients doing regular exercise (0.009*) and a good sleep pattern (0.000*) help in the reduction of SBP at 0.05 level of significance. Conclusion: The prevalence of hypertension is significant and regular exercise and good sleep habits can help hypertensive patients to lower their SBP.